A silent killer or an overrated problem? Epidemiological trends in hypertension, including Poland - Tradecki, Marek; Parfianowicz, Agnieszka; Surma, Alicja; Szyszka, Michał; Poręba, Rafał; Gać, Paweł (Journal of Health Inequalities, 2025)
The primary objective of this study is to demonstrate that arterial hypertension continues to constitute a significant public health challenge in the 21st century. Hypertension, often referred to as a “silent killer”, remains one of the most significant global health challenges, contributing to cardiovascular diseases such as stroke, heart attack, and kidney failure. Despite advancements in medical knowledge, hypertension is underdiagnosed and poorly controlled worldwide, including in Poland. Hypertension is still a significant problem in the country, affecting 35.2% of adults. Many Polish patients often express the sentiment: “If you can’t see it, it doesn’t exist.” Globally, less than half of adults are aware that they have hypertension. This article examines the epidemiological trends of hypertension, emphasizing its modifiable risk factors such as physical inactivity, high sodium intake, obesity, and excessive alcohol consumption. Both lifestyle modifications – such as increased physical activity, a heart-healthy diet and smoking cessation – and pharmacological interventions are crucial in managing and preventing hypertension. In Poland, as elsewhere in the world, single-pill combination therapies are becoming the standard for effective treatment adherence. Reaching global hypertension control targets, including reducing harmful alcohol use, tobacco consumption, physical inactivity, and sodium intake, is essential to mitigate the morbidity and mortality associated with hypertension. Through coordinated interventions and public health strategies, substantial progress can be made in reducing the global burden of this preventable condition.